1989
DOI: 10.1007/bf02624138
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of collagen by human fibroblasts and keratinocytes

Abstract: In the process of wound healing keratinocytes and fibroblasts play an important role, keratinocytes in the re-epithelization process and fibroblasts in the process of wound contraction. We have studied the role of human keratinocytes and fibroblasts in the rearrangement of collagen in a collagen lattice model system. Our results revealed that keratinocytes as well as fibroblasts rearrange the collagen lattice; this occurs in a cell number and collagen concentration dependent manner. The optimal gel contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 19 publications
2
20
0
2
Order By: Relevance
“…The ability of normal colon fibroblasts to contract a collagen lattice was markedly enhanced in the presence of colon cancer cells. Interestingly, a reduction of gel size which is greater than the sum of the contraction induced by individual cell types has also been reported recently for co-cultures of human keratinocytes and fibroblasts using visual estimates of gel size (Souren et al, 1989).…”
Section: Discussionsupporting
confidence: 63%
“…The ability of normal colon fibroblasts to contract a collagen lattice was markedly enhanced in the presence of colon cancer cells. Interestingly, a reduction of gel size which is greater than the sum of the contraction induced by individual cell types has also been reported recently for co-cultures of human keratinocytes and fibroblasts using visual estimates of gel size (Souren et al, 1989).…”
Section: Discussionsupporting
confidence: 63%
“…The spindle-type morphology of the HFs in the HDE gels was consistent with HFs grown in a collagen lattice. 28 Thus, when the HFs were seeded into the three-dimensional collagen lattice they left the mitotic cell cycle and became growth-regulated. This is in agreement with Sarber et 01.…”
Section: Discussionmentioning
confidence: 99%
“…The possible involvement of keratinocytes in wound remodeling was suggested by Souren et al 11 in 1989. These authors reported that collagen gels could be rearranged if keratinocytes were seeded on their surfaces, an effect that was not observed if the cells were seeded inside a gel.…”
Section: Introductionmentioning
confidence: 93%